The soft power implications of the new South Korean cinema: Approaching audiences in East Asia and Lithuania - Juknevičiūtė, Laima (Acta Orientalia Vilnensia, 2011)
Vytautas Magnus University South Korea’s experience wielding soft power is usually associated with the Korean Wave, which swept the Asian region off its feet predominantly during the first decade of this century. In this article I will however argue that the phenomenon of the Korean Wave has never been intended as a calculated attempt on the part of the South Korean government to enhance the overall South Korean image worldwide and thus increase South Korean international might and prestige. To prove the validity of this hypothesis, I will provide a concise historical overview of the inception, development and spread of South Korean popular culture, while at the same time tracing its underlying soft power implications. I will likewise attempt to discuss the popular reception of the Korean Wave in three East Asian countries, i.e. Mainland China, Taiwan and Japan, and one European country, i.e. Lithuania. The scope of the endeavour has been largely restricted to the cinematic aspect of the Korean Wave, for I consider the creation of motion pictures and drama serials to be by far the most precious, influential and revealing form of art.